PREVENTION OF NOSOCOMIAL PNEUMONIAS IN A SURGICAL INTENSIVE CARE UNIT - O. A. Orlova; V. G. Akimkin (Сеченовский вестник)
Nosocomial pneumonia on average occurs in 8–20% of patients in the Intensive care unit (ICU) and in 27% of patients under mechanical ventilation (ventilator). The pnemonia prevalence depends on the duration of respiratory support, and is an independent predictor of adverse outcome in critically ill patients requiring mechanical ventilation. The study objective is to develop measures to prevent nosocomial ventilator-associated pneumonias (VAP) in surgical intensive care units. We analyzed the measures to prevent ventilator-associated respiratory tract infections in the surgical intensive care department (ICU) for 10 years (2004–2013). The prevalence of ventilator-associated respiratory tract infections is the highest (87.65±11.76%) in the stucture of health care-associated infections. The improved surveillance system produced the reliable data on the incidence density (increase from 3.9±0.8 in 2004 and 11.7±1.4 in 2007, per 1 000 ALV/day). Pathogens VAP were characterized by multiple drug resistance. The greatest resistance was found to aminoglycosides in the isolated microorganisms (69.5±6.8%). The percentage of desinfectant resistant strains ranged from 1.1±0.6% (chlorine-based disinfectants) to 13.13±4.8% (to quarternary ammonium based disinfectants). VAP prevention in the surgical ICU should be comprehensive and include a hospital-wide preventive measures.